IMPROVING LISTENING COMPREHENSION OF NARRATIVE TEXTS THROUGH THE DICTOGLOSS METHOD IN ENGLISH LANGUAGE TEACHING - Peni Latifah; Wijayadi (PROCEEDING UMSURABAYA, 2026)
:This study aims to improve the listening comprehension skills of class X-6 students of SMAN 17 Surabaya through the application of the dictogloss method in narrative text learning. The dictogloss method integrates listening and writing skills collaboratively through the process of listening, recording keywords, and text reconstruction. This study uses the Classroom Action Research (CAR) approach in one cycle that includes the stages of planning, implementation, observation, and reflection. Data were collected through pretest and posttest, as well as observation during the learning process. The results of the descriptive statistical analysis showed an increase in the average score from 86.3 (pretest) to 94.67 (posttest), with an average gain of 8.37 points. Learning completeness increased from 80% to 100%. These findings indicate that the dictogloss method is effective in improving students' listening skills, as well as building active participation and cooperation in learning. This study recommends the use of the dictogloss method as a continuous learning strategy in teaching narrative text in English classes.